Double Compressions of Atmospheric Depth by Geopotential Tendency, Vorticity, and Atmospheric Boundary Layer Affected Abrupt High Particulate Matter Concentrations at a Coastal City for a Yellow Dust Period in October - Hyo Choi; Mi Sook Lee (Advances in Meteorology)
Using GRIMM-aerosol sampler, NOAA-HYSPLIT model, and 3D-WRF-3.3 model, the transportation of dusts from Gobi Desert toward Gangneung city, Korea was investigated from 09:00 LST October 27 to 04:00 LST October 28, 2003. Maximum PM10 (PM2.5, PM1) concentration was detected with 3.8 (3.4, 14.1) times higher magnitude than one in non-Yellow Dust period. The combination of dusts transported from the desert under westerly wind with particulate matters and gases from vehicles on the road of the city caused high PM concentrations near the ground surface at 09:00 LST and their maxima at 17:00 LST near sunset with further pollutants from heating boilers in the resident area. Positive geopotential tendency at the 500 hPa level of the city (∂Φ/∂t; m day−1) corresponding to negative vorticity of -4×10-5 sec−1 (-2.5×10-5 sec−1) at 0900 LST (21:00 LST; at night) was +83 m day−1 (+30 m day−1) and it caused atmospheric depth between 500 hPa level and the ground surface to be vertically expanded. However, its net reduction to −53 m/12 hrs until 21:00 LST indicated synoptic-scale atmospheric layer to be vertical shrunken, resulting in the increase of PM concentrations at 17:00 LST. Simultaneously, much shallower microscale stable nocturnal surface inversion layer (NSIL) than daytime thermal internal boundary layer induced particulate matters to be merged inside the NSIL, resulting in maximum PM concentrations at 17:00 LST.